Pengaruh Model Pembelajaran Guided Note Taking (GNT) terhadap Kemampuan Komunikasi Matematis Siswa pada Materi Sistem Koordinat Kelas VIII SMP Negeri 3 Banda Aceh - Monadia Liiman (Neolectura, 2021)
Mathematics is one of the most important sciences, but the low mathematical communication ability of students is one of the problems found in SMP Negeri 3 Banda Aceh, especially in class VIII. To overcome this problem the researchers conducted a study using the Guided Note Taking (GNT) learning model this model is a learning model that involves students directly. The purpose of the study was to determine the mathematical communication skills of students who were taught with Guided Note Taking (GNT) were better than conventional learning models on the Coordinate System material in Class VIII SMP Negeri 3 Banda Aceh. This study uses a quantitative approach, while the type of research used is experimental and the design of this research is the Pre Test - Post Test Control Group design. The population in this study were all eighth grade students of SMP Negeri 3 Banda Aceh with a total of 5 classes. Sampling was done using random sampling technique, the samples in this study were students of class VIII-2 as the experimental class and class VIII-1 as the control class with 24 people in each class. The research instrument used was Pretest, Observation, Posttest, and the data were analyzed using t-test statistics. The results of the Pretest and Posttest were carried out with normalized gain aiming to see the effect that occurred between the experimental class and the control class by testing the hypothesis using the t-test at a significant level = 0.05, the final value of > was 2.23> 1.67 so criteria is rejected and is accepted. Thus, it can be concluded that students' mathematical communication skills taught by using the Guided Note Taking (GNT) learning model are better than students' mathematical communication skills taught by conventional learning on Coordinate System material in class VIII of SMP Negeri 3 Banda Aceh. The results of the observation activities observed by two observers in the experimental class and the control class at two meetings resulted in a satisfactory score, which was classified in the good category.